The alternate - Martel, John S. (New York : Signet, 1999)
In San Francisco, a woman prosecutor and a man defense lawyer face off in the case of a former congressman accused of murdering his wife. What neither realizes is their strategies will be upset by an alternate juror, a woman with her own agenda.
National College of Business and Arts
Keywords: Trials (Murder) -- Fiction; Fiction